Successful full-length genomic cloning and characterization of site-specific nick structures of Phytophthora endornaviruses 2 and 3 in yeast, Saccharomyces cerevisiae - Sakuta, Kohei; Uchida, Keiko; Fukuhara, Toshiyuki; Komatsu, Ken; Okada, Ryo; Moriyama, Hiromitsu (Frontiers in Microbiology, 2023)
Two endornaviruses, Phytophthora endornavirus 2 (PEV2) and Phytophthora endornavirus 3 (PEV3), have been discovered in pathogens targeting asparagus. In this study, we analyzed the nick structure in the RNA genomes of PEV2 and PEV3 in the host oomycetes. Northern blot hybridization using positive and negative strandspecific RNA probes targeting the 5' and 3' regions of PEV2 and PEV3 RNA genomes revealed approximately 1.0 kilobase (kb) RNA fragments located in the 5' regions of the two genomes. 3' RACE analysis determined that the size of the RNA fragments were 958 nucleotides (nt) for PEV2 and 968 nt for PEV3. We have successfully constructed full-length cDNA clones of the entire RNA genomes of PEV2 and PEV3 using a homologous recombination system in the yeast, Saccharomyces cerevisiae. These full-length cDNA sequences were ligated downstream of a constitutive expression promoter (TDH3) or a galactose-inducing promoter (GAL1) in the shuttle vector to enable the production of the full-length RNA transcripts of PEV2 and PEV3 in yeast cells. Interestingly, a 1.0 kb RNA fragment from the PEV3 positive-strand transcript was also detected with a 5'-region RNA probe, indicating that site-specific cleavage also occurred in yeast cells. Further, when PEV2 or PEV3 mRNA was overexpressed under the GAL1 promoter, yeast cell growth was suppressed. A fusion Nick structure in Endornavirus in Phytophthora spp.2 protein combining EGFP to the N-terminus of the full-length PEV2 ORF or C-terminus of the full-length PEV3 ORF was expressed, and allowed PEV2 and PEV3 ORFs to be successfully visualized in yeast cells. Expression of the fusion protein also revealed presence of heterogeneous bodies in the cells.